Mechanical Properties of Pediatric Knee Ligaments and The Iliotibial Band. Issue 5 (31st May 2022) - Sanchez, Mark; Gupta, Anshal; Rohde, Matt; Storaci, Hunter; Sherman, Seth; Ganley, Ted; Shea, Kevin
Background: Substantial research about the mechanical properties of adult knee ligaments exists, but comparatively little is known about the pediatric knee. Choosing a graft for ligament reconstruction in pediatric patients is limited by the lack of knowledge of the mechanical properties of those ligaments and potential graft options in the skeletally immature. Purpose: Describe the mechanical properties of the ACL, PCL, MCL, LCL, and iliotibial band (ITB) in pediatric patients. Methods: Skeletally immature fresh frozen whole knees from 18 human cadavers (mean specimen age = 10.4 years) were thawed and the ligaments grossly dissected with bone block attachments intact, and length, width, and thickness were measured. Specimens were tested as a single unit (for those containing multiple bundles) and hydrated throughout testing. Each specimen was secured in an MTS machine and underwent a tensile loading protocol to measure ultimate tensile strength, ultimate tensile strain, and linear modulus. Results: Under testing, the ACL exhibited ultimate tensile strength (8.7 +/- 4.1 MPa), ultimate tensile strain (54.4 +/- 20.8%), and linear modulus (31.0 +/- 22.8 MPa) that were similar to the PCL (9.8 +/- 6.6 MPa, 48.6 +/- 22.1%, and 47.9 +/- 53.5 MPa, respectively). The LCL ultimate tensile strength was 18.7 +/- 6.5 MPa, ultimate tensile strain was 57.2 +/- 22.2%, and linear modulus was 68.7 +/- 50.8 MPa, compared to the MCL (19.5 +/- 13.9 MPa, 38.9 +/- 15.7%, and 93.3 +/- 75.1 MPa, respectively). Finally, the ITB demonstrated an ultimate tensile strength of 11.8 +/- 4.4 MPa, ultimate tensile strain of 42.6 +/- 14.9%, and linear modulus of 55.5 +/- 27.7 MPa. Conclusion: The ITB demonstrated greater ultimate tensile strength and a higher linear modulus than the ACL and PCL, with a lower ultimate tensile strain. Conversely, the ITB demonstrated lower values for ultimate tensile strength and linear modulus than the LCL and MCL. The ITB may serve as a reasonable substitute for native ACL and PCL reconstruction due to similar ultimate tensile strengths. The ITB may be less well-suited to reconstruct the LCL and MCL due to more significant differences in ultimate tensile strength. Table 1. Demographics and select results of Pediatric Cadaver Specimens (n=18). MPa = megapascals. Figure 1. Biomechanical Strength of Ligaments in Pediatric Cadaver Specimens (n=18). Error bars indicate standard deviation.